Falling monuments, reluctant ruins : the persistence of the past in the architecture of apartheid - Judin, Hilton (Wits University Press, 2021)
Interrogates how, in the era of decolonisation, post-apartheid South Africa reckons with its past in order to shape its future. Architects, historians, artists, social anthropologists and urban planners seek answers in this book to complex and unsettling questions around heritage, ruins and remembrance. What do we do with hollow memorials and political architectural remnants? Which should remain, which forgotten, and which dismantled? Are these vacant buildings, cemeteries, statues, and derelict grounds able to serve as inspiration in the fight against enduring racism and social neglect? Should they become exemplary as spaces for restitution and justice? The contributors examine the influence of public memory, planning and activism on such anguished places of oppression, resistance and defiance. Their focus on visible markers in the landscape to interrogate our past will make readers reconsider these spaces, looking at their landscape and history anew.